DataView: Medicare Spending by State: The Border-Crossing Adjustment - Basu, Joy (CENTERS for MEDICARE & MEDICAID SERVICES, 1995)
As the first step in a pioneering effort by the Health Care Financing Administration (HCFA) to measure interstate border crossing for services used by both Medicare and non-Medicare beneficiaries, the authors study the spending behavior of Medicare beneficiaries for 10 Medicare-covered services. Based on interstate flow-of-expenditure data developed for calendar year 1991, the authors analyze the spending patterns of State residents by studying the inflow and outflow rates and the net flow ratios of expenditures incurred by Medicare patients. The report also provides per capita expenditure estimates with residence-based adjustments and evaluates the impact of the border-crossing adjustment for individual services and States.